Maize-based Diversified Cropping System for Higher Productivity and Profitability - Kumari, Megha; Singh, Teekam; Devi, Ayekpam Dollina (Chronicle of Bioresource Management, 2023)
Maize is a staple crop with significant economic and nutritional value, making it a crucial component of global agriculture. However, continuous monocropping can lead to soil degradation, pest infestations, and declining yields. Diversified cropping systems, which integrate maize with complementary crops, offer a sustainable approach to improving productivity and profitability. This system enhances soil fertility, optimizes resource utilization, and mitigates risks associated with climate variability and market fluctuations. By incorporating legumes, oilseeds, or vegetables alongside maize, farmers can achieve higher land-use efficiency and better income stability. Additionally, crop diversification reduces dependency on chemical inputs, promoting ecological balance and long-term sustainability.